Development of a parametric computer model for automating the production of power station dry ash dump growth plans. - Kreuiter, Andre (My University, 1998)
Generating growth plans for power station dry ash dumps having main and standby conveyor stacking systems is very time consuming using manual analysis methods. This usually prohibits investigating sufficient options or the routine evaluation of operating variations. Not achieving or changing any of the multitude ot geometric, physical or production design. assumptions over the 50 year construction life, can result in the dump growth deviating significantly from the original plan. Out of phase or too rapid long term growth situations can ensue, with costly modifications sometimes needed to return to acceptable growth plans or provide additional capacity. It was postulated that a parametrically driven computer model would facilitate rapid and cost effective dump growth evaluation. This dissertation documents the development of a prototype, spreadsheet-based, parametric modeling program for automating the production of dry ash dump growth plans. The system showed that sensitivity, optimisation and routine evaluation exercises now become practicable.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of science in Engineering.
Keywords: Ash disposal.